Design of the env-su Gene Coding for Surface Unit Protein as a Vaccine Candidate for Jembrana Disease Virus in In Silico - Nur Asih Setiarini; Indriawati Indriawati; R Susanti Susanti; Endang Tri Margawati (Jurnal Riset Biologi dan Aplikasinya, 2021)
Bali cattle are superior meat producers, but they are susceptible to Jembrana disease. The injection of the crude vaccine was considered ineffective, so the env-su gene was selected to express the Jembrana Surface Unit (JSU) protein as a candidate for the Jembrana vaccine. This study aimed to analyze the potential of the JSU protein as a candidate for the Jembrana vaccine and analyze the increase in the env-su gene expression which codon has been optimized in silico. Vaccine design was carried out through in silico including the selection of the SU protein sequences of the genus Lentivirus and sequence alignment of UniProt. The construction phylogeny tree of SU protein using MEGA-X program, optimization of env-su gene codon with preference codon Esherichia coli str. K-12 substr. MG1655 using Optimizer. The optimized env-su gene was inserted into the plasmid pET-21a (+) using GenScript. The result of sequence alignment showed that there is no SU protein that has a percent identity value of more than 30% with JSU protein. The SU JDV and BIV proteins are monophyletic groups and have a percent identity of 20.57%. Codon optimization showed an increase in CAI by 1,000 and GC 54.5%, and a decrease in ENc to 22 and AT 45.5%. EcoR1 and HindIII can recognize the gene target and MCS cut regions on the plasmid so that the env-su gene can be inserted into the pET-21a (+) plasmid. The JSU protein has the potential to be a candidate for the Jembrana vaccine, but it needs further research in vitro and in vivo.